CAPITALISM: ITS VARIETIES AND RELATIONSHIP WITH THE CORRUPTION PERCEPTIONS INDEX - Šečkutė, Vaiva; Giedraitis, Vincentas R.; Rastenienė, Aušra (Ekonomika, 2014)
Given the current economic crisis and increasing competition both for foreign investment and in international markets, we think that this economic analysis is timely and useful as the corruption level is a significant factor in the investment decision-making process. In this article, we investigate whether different types of economic regulation (different types of capitalism) might be fostering corruption. We think that countries with the liberal market economics system might have a lower corruption. We use the theoretical approach of Hall, Soskice (2001) to the varieties of capitalism to analyse countries’ competitiveness according to the competitiveness indices of the World Economic Forum (WEF) and the International Institute for Development Management (IMD). We use the Knell and Srholec (2005) methodology to calculate the index of coordination that determines a country’s type of capitalism. The index consists of 9 variables which are later divided into 3 groups according to the factor analysis results. For the corruption estimate, we use the Transparency International corruption perceptions index. Regression analysis revealed that coordinated market economies (CME) are more conducive for corruption.